Australian water mites of the genus Hydrachna Müller, with the description of five new species (Acari: Hydrachnidia: Hydrachnidae) - Smit, Harry (Zootaxa, 2014)
A survey is given of the diversity of the water mite genus Hydrachna Müller in Australia. Five new species are described: Hydrachna cordata n. sp., H. curtiscutata n. sp., H. longiscutata n. sp., H. novaehollandica n. sp. and H. queenslandica n. sp.. The females of H. conjectoides Lundblad and H. hamata Lundblad and the male of H. tasmanica Lundblad are described for the first time. The conclusion of Lundblad (1947) that H. laceriscutata Lundblad is a synonym of H. bilobata is supported. Finally, many new records are given from Australian members of the genus.